Large‐scale control of the lower stratosphere on variability of tropical cyclone intensity. Issue 9 (8th May 2017) - Ferrara, Madison; Groff, Faith; Moon, Zach; Keshavamurthy, Kushal; Robeson, Scott M.; Kieu, Chanh
Abstract: Recent studies of tropical cyclones (TC) have suggested intricate impacts of the lower stratosphere layer (LSL) on TC development at the high‐intensity limit. This study examines the potential realization of the impacts of the LSL interannual variability on TC intensity. By minimizing the effects of sea surface temperature and outflow temperature based on the potential intensity framework, partial correlation analyses show a negative correlation between the power dissipation index (PDI) for intense TCs and the tropopause height in the northwestern Pacific basin but a weaker relationship in the north Atlantic basin. Similar analyses for the LSL stratification also reveal signals of negative correlations between the LSL stratification and PDI in both basins, corroborating recent modeling studies about the impacts of the LSL on TC development. Due to the complexity of the relationships and data limitations, however, all correlations are statistically insignificant, thus rendering the impacts of LSL on TC intensity inconclusive at present. Plain Language Summary: This study presents analyses of the statistical relationship between tropical cyclone intensity and the interannual variability of the lower stratosphere. By isolating the dominant impacts of sea surface temperature and outflow temperature, it is shown that there is a signal of inverse relationship between the tropopause height and the power dissipation index (PDI) for intense TCs. This inverse relationship is however more apparent in the northwestern Pacific basin than in the North Atlantic basin. Likewise, similar inverse relationship is seen between the lower stratospheric stratification and the PDI, corroborating recent modeling studies about the impacts of the LSL on TC development. While all relationships are not statistical significance at present due to the multivariate nature of the PDI and limited data record, the results presented in this study suggest that the long‐term variability of the lower stratosphere could be a potential factor influencing the variability of TC intensity that has not been fully understood. Key Points: Variability in tropical tropopause height imposes potential influence on variations of tropical cyclone (TC) intensity Weaker stratification of the lower stratosphere tends to correspond to an increase in the power dissipation index of intense TCs Large‐scale impacts of the lower stratosphere on variability in TC intensity differ between ocean basins